Pengaruh Literasi Keuangan dan Pendapatan terhadap Keputusan Investasi: Pada Pelaku UMKM di Kecamatan Muara Sabak Barat Kabupaten Tanjung Jabung Timur - Rizky Andri Hermawan; Sissah Sissah; Attar Satria Fikri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In this research, carried out with the aim of finding out how financial literacy and income influence investment decisions in UMKM in Muara sabak barat District, East Tanjung Jabung Timur. This research uses a descriptive quantitative method and the data analysis method used is multiple linear regression. The sample used in this research was 30 UMKM. The results of the research show that partially financial literacy has a positive and significant influence on the investment decisions of UMKM actors and income has a significant influence on the investment decisions of UMKM actors. Simultaneously Financial Literacy and Income have a positive and Significant influence on Investment decisions of UMKM players. The resukts of calculating the coefficient of determination show that financial literacy and income on investment decisions have an influence of 55.4% and the remaining 44.6% is influenced by other variables outside this search.